Job crafting : the art of redesigning a job - De Gennaro, Davide (Emerald points., 2019)
Although most jobs are initially designed by managers, employees also play an important role in this phase through a proactive behavior called 'job crafting'. It describes a bottom-up approach that consists of customizing and modifying structural, relational, and cognitive aspects of one's job to match personal skills, attitudes, and inclinations. The literature on this subject has been developing for over 20 years but requires a recapitulation to bring together different and often disconnected contributions and provide a concise research agenda for scholars wishing to approach the study of these issues. This book provides a conceptual framework on job crafting by demonstrating how its practice results in a more meaningful and satisfying work experience. This book is the first to investigate this area of study in such a complete and exhaustive way: it takes a managerial perspective to identify the antecedent and outcome variables of job crafting and suggests behaviors which managers should steer clear from to avoid facing negative and unexpected consequences.